THE ROLE OF THE KARIMUN RESORT POLICE TRAFFIC UNIT IN PREVENTING VIOLATIONS AND CONTROLLING TRAFFIC (Case Study of Motorized Vehicle Users for Minors) - Roli Sambuardi; Azmi; Deska Zulkarnain; Andri Setiawati (Yayasan Wayan Marwan Pulungan, 2024)
This research begins with the researcher's view of the field phenomenon where there are still many legal violations in traffic problems in the Karimun area. The implementation of regulations has not been able to maximize the deterrent effect on minors in Karimun.This research aims to find out the role of the Karimun Resort police traffic unit in preventing violations and controlling motor vehicle traffic for minors. Data was collected using unstructured interviews, documentation, and observation. Data analysis in this research uses data analysis techniques on the Miles Huberman website, the data that has been collected is created in a matrix, using qualitative analysis research methods. This research uses the theory developed by Biddle and Thomas regarding the role of policy, the role of strategy, the role of a communication tool, the role of dispute resolution, and the role of therapy.The results of this research regarding the role of traffic police in preventing violations and controlling traffic can be said to be quite good because according to what the researchers heard from the traffic police, they have implemented them following applicable policies and regulations. It just requires the role of parents and the school environment to be able to emphasize to their children not to drive motorized vehicles before the specified age and vehicle users must at least have a driver's license.